2008
DOI: 10.1080/01904160801926848
|View full text |Cite
|
Sign up to set email alerts
|

Biofumigant Biomass, Nutrient Content, and Glucosinolate Response to Phosphorus

Abstract: Information on biofumigant-green manure vegetative biomass, nutrient, and glucosinolate content sensitivity to phosphorus (P) is lacking for species used in potato and sugarbeet production. Therefore, available P effects on field-grown condiment yellow mustard (Sinapis alba, cv. IdaGold) and oilseed radish (Raphanus sativa, cv. Colonel) were evaluated (2001-03). Low soil P was generally more limiting to radish foliage P concentrations or uptake than to the mustard, suggesting inherent differences in their abil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
2
3
0
Order By: Relevance
“…We did not fi nd any other studies reporting P uptake by forage radish cover crops in the literature; however, reports of P uptake of oilseed radish (Raphanus sativus L. var. oleiferus), a close relative of forage radish with similar characteristics, are similar to our P uptake fi ndings (Brown et al, 2008;Wang et al, 2008). Brown et al (2008) also found that P uptake by oilseed radish increased in response to P fertilizer applications.…”
Section: Discussion Cover Crop Phosphorus Contentsupporting
confidence: 89%
See 1 more Smart Citation
“…We did not fi nd any other studies reporting P uptake by forage radish cover crops in the literature; however, reports of P uptake of oilseed radish (Raphanus sativus L. var. oleiferus), a close relative of forage radish with similar characteristics, are similar to our P uptake fi ndings (Brown et al, 2008;Wang et al, 2008). Brown et al (2008) also found that P uptake by oilseed radish increased in response to P fertilizer applications.…”
Section: Discussion Cover Crop Phosphorus Contentsupporting
confidence: 89%
“…oleiferus), a close relative of forage radish with similar characteristics, are similar to our P uptake fi ndings (Brown et al, 2008;Wang et al, 2008). Brown et al (2008) also found that P uptake by oilseed radish increased in response to P fertilizer applications. In our experiment, the soil test P values were in the optimum range for crop production.…”
Section: Discussion Cover Crop Phosphorus Contentsupporting
confidence: 89%
“…This indicates that P might have been released through decomposition of the pennycress biomass, which is in line with the interpretation above that N was mineralized from oilseed biomass. Blackshaw et al (2004) reported P concentrations in field pennycress biomass ranged from 1.5 to 1.7 g kg −1 , which is considerably more than the 0.3 to 0.5 g kg −1 reported for oilseed radish (Brown et al, 2008), but only slightly more than the 1.2 to 1.4 g kg −1 reported for winter rye (Karasawa and Takahashi, 2015). All of these values are below the range of P concentrations in the cover crop shoot biomass sampled in the current study.…”
Section: Discussionmentioning
confidence: 85%
“…Coincidentally, in rocket salad ( Eruca sativa ), Chun et al (2017) found that applications of N and P at low concentrations, or higher concentrations of potassium enhanced the synthesis of total GLs; in particular 5 and 2 mM N and P possessed much higher levels of several types of aliphatic GLs than other nutrient concentrations tested. On the contrary, in yellow mustard ( Sinapis alba ) and oilseed radish ( Raphanus sativa ), P effects on GLs producing ionic or isothiocyanates were relatively insignificant (Brown et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Ida Gold) and radish ( Raphanus sativa cv. Colonel), and these crops differ significantly in their ability to uptake and accumulate P (Brown et al, 2008). However, P deficiency does increase the total GL concentration in B. campestris L. subsp.…”
Section: Introductionmentioning
confidence: 99%